Lived Experiences of Parents/Guardians of Children with Neuro- developmental Disorders: Concept Paper - Tsomondo, Ethel; Chihava, Itai; Zvinavashe, Mathilda; Mugadza, Gladys; Makoni, Petty (IJRDO - Journal of Social Science and Humanities Research, 2017)
Parents /Guardians of children with Neurological Disorders encounter physical, psychological, social and financial negative experiences throughout their process of parenting children with neurological deficit.Methodology Walker and Avant (2011) concept analysis model was used as a guide. Literature search was done using the following search engines, Google Scholar, PubMed, and Medline and 43 articles which  ranged from 1994– 2017 were identified. The researchers settled for 30 articles that were found relevant to the concept of interest.